The collectin SP-A and its trimeric recombinant fragment protect alveolar epithelial cells from the cytotoxic and proinflammatory effects of human cathelicidin in vitro - de Tapia, Lidia; García-Fojeda, Belén; Kronqvist, Nina; Johansson, Jan; Casals, Cristina (Frontiers in Immunology, 2022)
Human cathelicidin (LL-37) is a defense peptide with antimicrobial activity against various pathogens. However, LL-37 can also trigger tissue injury by binding to host cell membranes. The cytotoxic effects of LL-37 may be especially relevant in chronic respiratory diseases characterized by increased LL-37. The aim of this study was to investigate whether the human collectin SP-A and a trimeric recombinant fragment thereof (rfhSP-A) can regulate the activities of LL-37. To this end, we studied the interaction of LL-37 with SP-A and rfhSP-A by intrinsic fluorescence, dynamic light scattering, and circular dichroism, as well as the effects of these proteins on the antimicrobial and cytotoxic activities of LL-37. Both SP-A and rfhSP-A bound LL-37 with high affinity at physiological ionic strength (KD = 0.45 ± 0.01 nM for SP-A and 1.22 ± 0.7 nM for rfhSP-A). Such interactions result in the reduction of LL-37-induced cell permeability and IL-8 release in human pneumocytes, mediated by P2X7 channels. Binding of LL-37 to SP-A did not modify the properties of SP-A or the antibacterial activity of LL-37 against respiratory pathogens (Klebsiella pneumoniae, Pseudomonas aeruginosa, and nontypeable Haemophilus influenzae). SP-A/LL-37 complexes showed a greater ability to aggregate LPS vesicles than LL-37, which reduces endotoxin bioactivity. These results reveal the protective role of native SP-A in controlling LL-37 activities and suggest a potential therapeutic effect of rfhSP-A in reducing the cytotoxic and inflammatory actions of LL-37, without affecting its microbicidal activity against Gram-negative pathogens.